Du Zaïre a la R.D. Du Congo: la Vieille Termitiere Terrassee par le vent de la Savane - Kennes, Erik (Afrika Focus, 1997)
This article concentrates mainly on the internal sources of the rapid breakdown of the Zairian state apparatus, deliberately not taking into account regional and international support for the warring parties. The Zairian state has been unable to manage its internal contradictions. This was driven to an extreme in the Kivu region, where the deeply seated crisis of representation was never adequately resolved. The absence of conflict-regulating institutions at the regional level was one enabling element for the rapid expansion of the Kivu conflict into its regional and international ramifications. Another was the absence of any workable political alternative to armed struggle on the national level; neither the opposition, nor the government or the presidency was able to impose itself. In the general context of state decay, part of which was the implosion of the army, newcomers in the mining industry have initiated a take-over of key sectors of the Zairian economy, probably inducing a new mode of governance in the country. KEY-WORDS: Congo, economy, politics, Zaire